A visão do orientador educacional acerca do papel social da escola - Fernandes, Marina Daipré Targa (2022)
The present work aimed to identify how guidance counselors (G.C.) conceive the social function of the school. For the production of the research, it was carried out a bibliographic review of recent academic studies in the area of guidance counseling, investigating also the social function of the school. A qualitative approach was used and a semi-structured script was utilized for interviewing three G.C., all of them working in private schools located in the city of São Paulo. The interviews were transcribed and analyzed through content analysis. The results showed that the G.C. have an important mediating role in promoting the students' socialization and subjectivation, which allowed to discuss the absence of these professionals in the public education networks and to show the contradictory position that, sometimes, they occupy within the private school. It was found that G.C. can fulfill the school‟s social function, strengthening their pedagogical role, despite the obstacles faced in defending school‟s values and pedagogical philosophy. However, due to the limited number of studies found and participants interviewed, more research should be carried out in this field, to broaden the understanding of such professional‟s work and function